Fungal succession in decomposing woody debris across a tropical forest disturbance gradient - Dossa, G.G.O.; Yang, Y.-Q.; Hu, W.; Paudel, E.; Schaefer, D.A.; Yang, Y.-P.; Cao, K.-F.; Xu, J.C.; Bushley, K.E.; Harrison, R.D. (Elsevier, 2021)
Fungi decompose woody debris, an important carbon pool in forests. Fungal community structure is expected to vary according to the wood species, habitats and extent of abiotic disturbance, which have consequences for carbon cycling in tropical forests. Here we examined the effects of fungal diversity and composition on woody debris decomposition rates and sought potential mechanisms to explain an observed lack of difference in decomposition rates across a disturbance gradient in a tropical montane rainforest in Xishuangbanna, SW China. We measured wood specific gravity (WSG) loss from 280 logs of Litsea cubeba and Castanopsis mekongensis over 3 years and monitored fungal communities from 418 samples using next-generation sequencing after 0, 18 and 36 months field exposure. Wood species and termite presence determined changes in fungal diversity through time. Overall there was a peak in fungal diversity at 18 mo, suggesting an initial period of colonization followed by a period of increasingly competitive interactions leading to decreased diversity. Litsea logs, which had relatively low initial WSG and thinner bark, harbored higher fungal diversity. Shared fungal OTUs between wood species peaked at 18 mo (~50%). However, fungal diversity was not a significant predictor of WSG loss. An effect of habitat on fungal community composition suggests that functional replacement explains the similar decay rates across the disturbance gradient. In addition, the proportions of saprotroph and white-rot fungi increased through time regardless of wood species. Termite presence reduced WSG loss, but the effect was mediated via the abundance of soft rot fungi. Our results suggest that changes in functional traits, rather than fungal species diversity, may better explain variation in WSG loss. Future studies should investigate roles of fungal functional traits and rot types, particularly those of Ascomycete fungi, whose roles in wood decay are still poorly characterized.